Hakikat Pengembalian Kerugian Negara; Sebuah Penghukuman Buat Pelaku Atau Pemulihan Bagi Korban? - Rena Yulia (Lex LATA, 2020)
The phenomenon of returning state losses by corruptors has lately become a trend in the law enforcement process. Some of the returns were made during the investigation stage, during the trial process, some even after the verdict. As a result of returning state losses to perpetrators, among others, get a sentence reduction. However, sometimes the amount of return is not proportional to the total loss of the country as a whole. Therefore, the purpose of this paper is to examine the nature of the recovery of state losses intended to punish the perpetrators or to recover the losses of victims (the state). This will have an impact on the mechanism and effectiveness of returning state losses. This paper is expected to be able to describe in full the nature of the recovery of state losses so that they can be used as a basis for eradicating corruption. key word: corruption; state loss; return